Anthropophily of Malaria Vectors in Kahnouj District, South of Kerman, Iran - HR Basseri; SH Moosakazemi; S Yosafi; M Mohebali; H Hajaran; M Jedari (Tehran University of Medical Sciences, 2005)
This study was conducted to investigate hematophagic tendencies of the malaria vector based on a seasonal basis as well as by geographical region in a malaria endemic area in Kahnouj, southern Iran. This study was carried out for 14 months from Apr/ 2002 up to the end of May 2003. Female anophelines were collected from different shelters in hilly and plain regions of Kahnouj district and their blood meal was tested using ELISA test methods. The five vectors that were active in the study area consisted of An. fluviatilis, An. stephensi, An. dthali, An. culicifacies, and An. superpictus. The dominant Anopheline in hilly areas was An. fluviatilis sibling species T. This species was active during whole year and reached a peak in December. In contrast the dominant species in flat regions was An. stephensi which showed strongly endophilic behavior with two seasonal activity peaks. The anthropophilic index for An. fluviatilis and An. stephensi was estimated at 2.68% and 0.5%, respectively. The population of other species was too low and they did not show a propensity for human blood. The most malaria cases occurred in the hilly area where An. fluviatilis is the active dominant species. It seems that An. fluviatilis is responsible for transmission of malaria in hilly districts of Kahnouj. Thus malaria transmission in this study area is much influenced by resident's rest habits while a wild vector, An. fluviatilis shows exophilic behavior and uses microclimate shelters with high incidence of human blood feeding. Thus, adapting people to use personal protection such as a bed net instead of residual spraying may be considered as an effective measure in malaria control in hilly regions.